Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of total and alkali-soluble calcium and magnesium contents of crude sodium borates (titrimetric method) Part 29, (31st July 1986) - British Standards Institution,
No abstract available